Structural, optical and electrical properties of In2(Te1-xSex)3 thin films. (January 2018) - Pandian, M.; Matheswaran, P.; Gokul, B.; Sathyamoorthy, R.; Asokan, K.
Abstract: Indium chalcogenide In2 (Te0.975 Se0.025 )3, In2 (Te0.95 Se0.05 )3 and In2 (Te0.9 Se0.1 ) thin films was prepared by thermal evaporation technique in Ar atmosphere. The samples were analyzed by XRD, transmittance spectra, FESEM, DSC and EDS in order to investigate the structural, optical properties, surface morphology, phase identification and elemental composition of the prepared films. XRD spectra reveal that the formation of compounds of both the ternary phase of In2 (Te1-x Sex )3 and the binary phases of In2 Se3 and In2 Te3 . Improvement in crystallite size is observed with increase in the elemental composition of Se concentration. The surface morphology of the as grown film shows spherical nature of the grains and it becomes denser with the increase in Se concentration. Band gap energy was estimated from optical spectra, which depends on the phases of In2 Se3 and In2 (Te. Se)3 . and found to be 1.50 eV, which can be used for maximum absorption of an effective layer in solar cell. The broad exothermic peaks at 675 K, 683 K and the sharp peak at 694 K, which clearly confirms the presence of crystalline In2 (Te1-x Sex )3 phase. The resistivity of In2 (Te1-x Sex )3 thin film was measured using four probe technique. The current increases progressively with temperature indicating the semiconducting nature of In2 (Te1-x Sex )3 thin films. Highlights: In2 (Te1-x Sex )3 thin films exists in both binary and ternary phases. At lower Se composition binary phase found dominant. Higher Se composition yields desired stoichiometric ternary phase. Se rich thin films show less activation energy of about 0.015 eV. Low activation energy of thin films are suitable for phase change memory devices.